N-butanol Subfraction of Brassica Rapa L. Promotes Reactive Oxygen Species Production and Induces Apoptosis of A549 Lung Adenocarcinoma Cells Via Mitochondria-dependent Pathway - Aipire, A; Chen, Q; Cai, S; Li, J; Fu, C; Ying, T; Lu, J; Li, J (MDPI AG, 2018)
Brassica rapa L., an edible and medical vegetable, has been traditionally used in Uyghur folk medicine to treat coughs and asthma in the Xinjiang Uygur Autonomous Region, China. In this study, we prepared an n-butanol subfraction of B. rapa L. (BRBS) and investigated the anti-tumor effect on A549 lung adenocarcinoma cells. The proliferation of A549 cells was significantly inhibited by BRBS treatment in a dose- and time-dependent manner. BRBS significantly induced cell cycle arrest and apoptosis in A549 cells through increased reactive oxygen species (ROS) production and mitochondrial dysfunction characterized by a reduction in mitochondrial membrane potential and the release of cytochrome c, which promoted caspase-3 and poly(ADP-ribose) polymerase processing. Moreover, BRBS significantly suppressed the migration of A549 cells in vitro. These results suggest that BRBS inhibited A549 cell proliferation through increased ROS production and the mitochondria-dependent apoptosis pathway. Consequently, BRBS might be a potential candidate for the treatment of lung cancer.
Keywords: Brassica rapa L.; Antitumor; Reactive oxygen species; Apoptosis; Cell cycle arrest; Migration